Scout extracurricular activity: A positive effect on students’ potential entrepreneurial character - Maulana Mega Hapsari (Universitas Negeri Yogyakarta, 2022)
Scout extracurricular activity in the education world can create entrepreneurship as indicated by working hard, discipline, responsibility, independence, creativity, motivation to be successful, and innovativeness. This study was aimed to examine scout extracurricular activity effect on the potential entrepreneurial character of students at junior high schools in Indonesia. This research employed a qualitative approach with a case study research design. This research was conducted in junior high schools in Sumatra, Java, Kalimantan, Sulawesi, Nusa Tenggara, Bali, and Papua. About 700 students were employed as the sample. The sample was selected using a random sampling technique. Instrument in the form of questionnaire was distributed to the participants using google form. The result of the research shows that 83% of respondents strongly agree with Scout extracurricular activity. 86% of respondents strongly agree with the positive effect of perceived entrepreneurial spirit. Overall, scout extracurricular activity can contribute positively to the entrepreneurial character in junior high school students.